Clinical and physiological assessments for elucidating falls risk in Parkinson's disease - Latt, Mark D.; Lord, Stephen R.; Morris, John G.L.; Fung, Victor S.C. (Movement disorders, 2009)
The study aims were to devise (1) a fall risk screen for people with PD using routine clinical measures and (2) an explanatory (physiological) fall risk assessment for guiding fall prevention interventions. One hundred thirteen people with PD (age 66 ± 95% CI 1.6 years) underwent clinical assessments and quantitative tests of sway, gait, strength, reaction time, and lower limb sensation. Participants were then followed up for 12 months to determine fall incidence. In the follow‐up year, 51 participants (45%) fell one or more times whereas 62 participants (55%) did not fall. Multivariate analyses of routine clinical measures revealed that a fall in the past year, abnormal axial posture, cognitive impairment, and freezing of gait were independent risk factors for falls and predicted 38/51 fallers (75%) and 45/62 non‐fallers (73%). A multivariate model combining clinical and physiological measures that elucidate the pathophysiology of falls identified abnormal posture, freezing of gait, frontal impairment, poor leaning balance, and leg weakness as independent risk factors. This model correctly classified 39/51 fallers (77%) and 51/62 non‐fallers (82%). Patients with PD at risk of falls can be identified accurately with routine clinical assessments and quantitative physiological tests. Many of the risk factors identified are amenable to targeted intervention. © 2009 Movement Disorder Society